The Utility of the SCAS-C/P to Detect Specific Anxiety Disorders Among Clinically Anxious Children - Reardon, Tessa (Psychol Assess, 2019)
Questionnaire measures offer a time and cost-effective alternative to full diagnostic assessments for identifying and differentiating between potential anxiety disorders and are commonly used in clinical practice. Little is known, however, about the capacity of questionnaire measures to detect specific anxiety disorders in clinically anxious preadolescent children. This study aimed to establish the ability of the Spence Children’s Anxiety Scale (SCAS) subscales to identify children with specific anxiety disorders in a large clinic-referred sample (N = 1,438) of children aged 7 to 12 years. We examined the capacity of the Separation Anxiety, Social Phobia, Generalized Anxiety, and Physical Injury Fears (phobias) subscales to discriminate between children with and without the target disorder. We also identified optimal cutoff scores on subscales for accurate identification of children with the corresponding disorder, and examined the contribution of child, mother, and father reports. The Separation Anxiety subscale was able to accurately identify children with separation anxiety disorder, and this was replicated across all 3 reporters. Mother- and father-reported Social Phobia subscales also accurately identified children with social anxiety disorder, although child report was only able to accurately detect social anxiety disorder in girls. Using 2 or more reporters improved the sensitivity of the Separation Anxiety and Social Phobia subscales but reduced specificity. The Generalized Anxiety and Physical Injury Fears subscales failed to accurately identify children with the corresponding disorders. These findings have implications for the potential use of mother-, father-, and child-report SCAS subscales to detect specific disorders in preadolescent children in clinical settings.